Determination of nitrogen compounds in water for human consumption in the municipality of Itacoatiara-Am using methodologies based on digital images. (REMUNOM, 2024)
Nitrogen compounds: nitrate (NO3-), nitrite (NO2-) and ammonia (NH3), when in excess in water, make it unfit for consumption. Ingestion of water contaminated by these compounds causes diseases such as: methemoglobin, breast cancer, stomach, breast cancer and bladder cancer. Ammonia is easily adsorbed on soil particles and is generally found in groundwater or shallow water. The presence of ammonia is important in the method of disinfecting water using chlorine, through the formation of chloramines, which have low bactericidal power. Excess nitrite in water presents a health hazard, as it can cause methemoglobinemia in newborns and even adults with enzyme deficiency. Nitrate is capable of being converted to nitrite by the action of some enzymes in saliva and specific bacteria according to the reaction. Nitrite, nitrate and ammonia can be determined by UV-Vis spectrophotometry. In this project, a study of the nitrite, nitrate and ammonia content in water for human consumption was proposed using methodologies based on digital images. The water quality parameters analyzed were: nitrite, nitrate and ammonia, both with the developed photometer and with the reference method, UV-VIS spectrophotometry. The results obtained by the two methodologies present a small discrepancy with an absolute relative error of 6.0%. All samples presented nitrite, nitrate and ammonium levels below the maximum value allowed by Ordinance No. 888/2021 of the Ministry of Health for drinking water.